IN VITRO STUDIES ON HEME OXYGENASE-1 AND P24 ANTIGEN HIV-1 LEVEL AFTERHYPERBARIC OXYGEN TREATMENTOFHIV-1 INFECTED ON PERIPHERAL BLOOD MONONUCLEAR CELLS (PBMCS) - Budiarti, Retno; Kuntaman, Kuntaman; Nasronudin, Muhammad; suryokusumo, muhammad guritno; Khairunisa, Siti Qamariyah (African Journal of Infectious Diseases (AJID), 2018)
Background: Heme oxygenase-1 (HO-1) is a protein secreted by immune cells as a part of immune response mechanism.HO-1 can be induced by variety agents that causingoxidative stress, such as exposure to 100% oxygenat2,4 ATA pressure.It plays a vital role in maintaining cellular homeostasis.This study was conducted to identify the effect of hyperbaric oxygen exposure in cultured ofPBMCthat infected by HIV-1. Material and Methods: Primary culture of PBMCs were isolated from 16 healthy volunteers and HIV-1 infected MT4 cell line by co-culture. The PBMCs were aliquoted into two wells as control group and treatment group. The 16 samples of HIV-1 infected PBMCwere exposed to oxygen at 2,4 ATA in animal hyperbaric chamber forthree times in 30 minutes periods with 5 minutes spacing period, that called 1 session. The Treatment done on 5 sessions within 5 days. 16 samples of HIV-1 infected PMBCs that have no hyperbaric treatment became control group.The supernatant were measured the HO-1 production by ELISA andmRNA expression of HO-1 by real time PCR and the number ofantigen p24 HIV-1by ELISA. Results: The result showed that there was no increasing of HO-1 at both mRNA level and protein level, there was a decreasing number of antigen p24 HIV-1 at the treatment group. In addition, hyperbaric exposure could not increase the expression of HO-1, more over the viral replication might be reduced by other mechanism. Conclusions: Hyperbaric oxygen could increases cellular adaptive response of PBMCs infected HIV-1 through increased expression of proteins that can inhibit HIV viralreplication.